2022
DOI: 10.3390/coatings12111703
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Concrete and Mortar Properties and Durability Using Pristine Graphene Particles

Abstract: The usage of industrially generated graphene was explored in this work, with an emphasis on dosage effects on durability, as well as the mechanical and microstructural properties of both concrete and mortar (0%, 0.1%, and 0.2% in concrete and 0%, 0.07%, and 0.15% in mortar). Based on the mix design for wastewater infrastructure, the results showed that adding graphene to both concrete and mortar enhanced 28-day compressive strength by 10–20%, with the best admixture level being 0.02–0.1%. Graphene reduced the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…However, they noted a decrease in strength at a 0.20% admixture level, likely attributable to graphene oxide agglomeration. Further corroborating these findings, Kirthi et al [15] found an optimal graphene dosage range of 0.02% to 0.1%, enhancing the concrete compressive strength by 10% to 20%. Despite these promising results, the high cost and difficulty in sourcing graphene limit its practical application in widespread engineering projects.…”
Section: Introductionmentioning
confidence: 63%
“…However, they noted a decrease in strength at a 0.20% admixture level, likely attributable to graphene oxide agglomeration. Further corroborating these findings, Kirthi et al [15] found an optimal graphene dosage range of 0.02% to 0.1%, enhancing the concrete compressive strength by 10% to 20%. Despite these promising results, the high cost and difficulty in sourcing graphene limit its practical application in widespread engineering projects.…”
Section: Introductionmentioning
confidence: 63%
“…Consequently, the exploration of advanced building materials exhibiting commendable mechanical properties, durability, and sustainability has emerged as a significant research focus within the realm of civil engineering . In recent years, the advent of nanomaterials has introduced novel approaches to address these challenges and enhance the comprehensive performance of cement-based materials. Graphene oxide (GO) is a two-dimensional nanomaterial consisting of carbon, hydrogen, and oxygen elements, with a large specific surface area and edge effect. Due to its multiple functional enhancements, GO is widely utilized in various fields such as building materials , and batteries , to improve the performance and function of other materials. Furthermore, GO has been employed in cementitious nanocomposites, owing to its exceptional properties. Mohammadreza Izadifar et al utilized tobermorite with a length of 14 Å as a model to create enhanced tobermorite nanocomposite materials by incorporating reduced graphene oxide (rGO).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the civil engineering community shifted their attention to developing high-performance mortar through different approaches. Traditional approaches, such as lowering the water/cement ratio, were adopted to minimize capillary and gel pores in the past [3]. Other researchers tried to incorporate steel fiber in a cement mortar mixture, which substantially enhances structural features, such as flexural strength and tensile strength [4].…”
Section: Introductionmentioning
confidence: 99%